What is the required level of detailedness in asylum narratives for the case to be deemed sufficiently detailed? - Heikola, Rebecca (My University, 2026)
Asylum interviews are used to evaluate if an asylum seeker faces persecution that meets the legal criteria for granting asylum. There are difficulties in assessing the asylum claims objectively. Guidelines direct asylum officials to use credibility indicators in their assessment, one of them being level of detail in the asylum seeker’s narrative. Although high level of detail can be a sign of telling the truth, the problem lies with drawing the line in when someone is being detailed enough. In this study, the aim was to investigate if the number of details elicited from the asylum interview could predict the Finnish Immigration Service’s assessment of detailedness. Secondary areas of interest were if the number of questions asked per topic, the proportion of open questions used and use of other credibility indicators affected the assessment of detailedness. The sample of the study consisted of Finnish asylum decisions with their interviews from 2017-2018. The decisions were divided to topics, i.e. events or experiences that are part of the asylum claim. Each topic was coded with number of details, assessment of detailedness, question amount, proportion of open questions, use of other credibility indicators, case outcome and credibility of the topic. A multinomial logistic regression model was created to test if the number of details could predict if the level of detail was deemed sufficient or not. The dependent variable was the Finnish Immigration Service’s assessment of detailedness, the categories being: 1) sufficiently detailed 2) insufficiently detailed 3) detail is not mentioned. The predictors were number of details, number of questions asked, proportion of open questions and amount of other credibility indicators. There was no statistically significant connection between number of details and the assessment of detailedness. However, number of questions, proportion of open questions and amount of other credibility indicators did predict which category the topic belonged to. The assessment of detailedness appeared to be subjective according to the results of this study, and the assessment was at chance level regardless of actual number of details elicited. This raised concern for the applicability of the criterion in credibility assessment. It should be used according to best practice standards, and its usability needs improving. The statistical analysis of this study had weaknesses, and all the results should be taken with caution and require replication, preferably with a new dataset. Still, this kind of research of the asylum system can help improve it towards a more objective and humane direction.

Turvapaikkapuhuttelua käytetään arvioimaan kohtaako turvapaikanhakija sellaista vainoa, joka vastaa turvapaikan saamisen laillisia vaatimuksia. On haastavaa arvioida turvapaikkahakemusta objektiivisesti. Suositukset ohjaavat virkailijoita käyttämään arviointiin uskottavuusindikaattoreita, joista tutkielman kohteena on yksityiskohtaisuuden taso turvapaikanhakijan kertomuksessa. Vaikka korkea yksityiskohtaisuuden taso voi olla merkki totuuden kertomisesta, ongelmallista on rajata, milloin joku on tarpeeksi yksityiskohtainen kertomuksessaan. Tässä tutkimuksessa tavoitteena oli tarkastella ennustaako turvapaikkapuhuttelussa esiintyneiden yksityiskohtien määrä Maahanmuuttoviraston arviota yksityiskohtaisuudesta. Toissijaisina kiinnostuksen kohteina olivat vaikuttavatko aiheesta kysyttyjen kysymysten määrä, avointen kysymysten osuus ja muiden uskottavuusindikaattorien käyttö Maahanmuuttoviraston arvioon yksityiskohtaisuudesta. Tutkimuksen otos koostui suomalaisista turvapaikkapäätöksistä puhutteluineen vuosilta 2017-2018. Päätökset jaoteltiin aiheisiin eli tapahtumiin tai kokemuksiin, jotka olivat osa turvapaikkahakemusta. Jokaiselle aiheelle koodattiin yksityiskohtien määrä, arvio yksityiskohtaisuudesta, kysymysten määrä, avointen kysymysten osuus, muiden uskottavuusindikaattorien käyttö, hakemuksen päätös ja aiheen uskottavuus. Multinomiaalinen logistinen regressiomalli muodostettiin tarkastelemaan, ennustaako yksityiskohtien määrä sitä, oliko yksityiskohtaisuuden taso arvioitu riittäväksi vai ei. Riippuva muuttuja oli Maahanmuuttoviraston arvio yksityiskohtaisuudesta, luokkina: 1) riittävän yksityiskohtainen 2) ei riittävän yksityiskohtainen 3) yksityiskohtaisuutta ei mainittu. Selittäjät olivat yksityiskohtien määrä, kysymysten määrä, avointen kysymysten osuus ja muiden uskottavuusindikaattorien määrä. Tilastollisesti merkitsevää yhteyttä yksityiskohtien määrän ja arvion yksityiskohtaisuudesta välillä ei ollut. Sen sijaan kysymysten määrä, avointen kysymysten osuus ja muiden uskottavuusindikaattorien määrä ennustivat mihin luokkaan aihe kuului. Tämän tutkimuksen tulosten perusteella arvio yksityiskohtaisuudesta vaikutti subjektiiviselta, ja arvio oli sattumanvarainen riippumatta puhuttelussa esiintyneiden yksityiskohtien määrästä. Tulos antaa syytä huoleen yksityiskohtaisuuden taso -kriteerin käytännön soveltumisesta uskottavuusarviointiin. Kriteeriä tulisi käyttää parhaiden käytäntöjen standardien mukaisesti, ja sen käytettävyys tarvitsee parantamista. Tämän tutkimuksen tilastoanalyyseissa oli heikkouksia, ja kaikki tulokset on ajateltava varovaisina arvioina, jotka tarvitsevat replikaatiota, mieluusti uudella otoksella. Silti tällainen tutkimus turvapaikkajärjestelmästä voi auttaa parantamaan sitä objektiivisempaan ja inhimillisempään suuntaan.
Keywords: asylum seeker; asylum procedure; level of detail; credibility assessment; decision making; memory retrieval